Moving from Inaction to Action: Challenging Homo- and Transphobia in Middle School English Language Arts - Henry (Cody) C. Miller; Kathleen M Olmstead; Kathleen Colantonio-Yurko; Amy Shema; Natalie Svrcek (Middle Grades Review, 2020)
What happens when teachers have opportunities to engage in LGBTQ-affirming practices but choose not to? In the following paper, the authors present a vignette from a middle school context and consider ways to challenge silences to support LGBTQ students in middle school English classrooms. The authors provide discussion and resources to help teachers engage in LGBTQ affirming practices with middle school students.
Keywords: LGBTQ-affirming pedagogies; responsive teaching practices; identity